2016
DOI: 10.1002/2015ja021567
|View full text |Cite
|
Sign up to set email alerts
|

Average field‐aligned current configuration parameterized by solar wind conditions

Abstract: We present the first large‐scale comparison of the spatial distribution of field‐aligned currents as measured by the Active Magnetosphere and Planetary Electrodynamics Response Experiment, with the location and brightness of the average auroral oval, determined from the Imager for Magnetopause‐to‐Aurora Global Exploration far ultraviolet instrument. These distributions are compared under the same interplanetary magnetic field magnitude and clock angle conditions. The field‐aligned currents and auroral oval dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
87
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 26 publications
11
87
0
Order By: Relevance
“…The average strength of these currents has been shown to be dependent on both IMF clock angle and magnitude (Anderson et al, 2008;Carter et al, 2016;Ganushkina et al, 2015;Weimer, 2001). The average strength of these currents has been shown to be dependent on both IMF clock angle and magnitude (Anderson et al, 2008;Carter et al, 2016;Ganushkina et al, 2015;Weimer, 2001).…”
Section: 1029/2019ja027249mentioning
confidence: 91%
See 1 more Smart Citation
“…The average strength of these currents has been shown to be dependent on both IMF clock angle and magnitude (Anderson et al, 2008;Carter et al, 2016;Ganushkina et al, 2015;Weimer, 2001). The average strength of these currents has been shown to be dependent on both IMF clock angle and magnitude (Anderson et al, 2008;Carter et al, 2016;Ganushkina et al, 2015;Weimer, 2001).…”
Section: 1029/2019ja027249mentioning
confidence: 91%
“…The average strength of these currents has been shown to be dependent on both IMF clock angle and magnitude (Anderson et al, 2008;Carter et al, 2016;Ganushkina et al, 2015;Weimer, 2001). This model is derived using magnetometer data from the CHAallenging Minisatellite Payload, Ø rsted, and Swarm satellite missions, which has created a database that spans more than 15 years.…”
mentioning
confidence: 99%
“…The global layout of the northern hemispheric magnetospheric current systems of the Earth, including the Region 1 and 2 currents (blue and red and downward and upward, respectively), magnetopause current (black), partial ring current (black dashed), and ionospheric Pedersen currents flowing across the polar cap (green). Figure reproduced with permission from Carter et al ().…”
Section: Introductionmentioning
confidence: 99%
“…The recent study of Carter et al [] performed an indirect comparison of FACs position, given by AMPERE, with auroral UV emissions, observed by IMAGE. This study (unexpectedly) revealed a discrepancy between the region 1 current location and auroral oval in the dusk sector.…”
Section: Introductionmentioning
confidence: 99%